PERLAWANAN ULAMA MINANGKABAU TERHADAP KOLONIALISME BELANDA ABAD XIX-XX - Syahrul Rahmat (UIN Imam Bonjol Padang, 2021)
The internal conflict between adat and religious (known as Paderi) groups in Minangkabau was initiated by the involvement of Dutch in the early 19th century. As requested by the Adat group to demolish the domination of Paderi, the Dutch had commenced to attack the Paderi group. Starting from that time, Ulama from religious groups had fought against the Dutch colonialism manifested in many forms of resistances. This study aims at reviewing types of resistance of Ulama in Minangkabau to the Dutch colonialization from the early 19th century until the early 20th century. Anchored in historical research methods involving heuristics, source criticism, interpretation and historiography, the data were analysed from the perspective of social conflict and history of thought. Finding reports the two types of resistance namely physical and non-physical ones triggered by various reasons i.e. religion, politics, economics and others.